Robust algorithm for electric fault diagnosis in the three phase induction machine based on spectral and wavelet tools. - Francisco Javier Villalobos Piña (Revista Iberoamericana de Automática e Informática Industrial RIAI, 2015)
This work present a group of tools based on the fast Fourier transform (FFT) and Haar, Daubechies and Coiﬂet discrete wavelet transform (DWT), using the Park's instantaneous space phasor module (ISP) of the three phase induction machine stator currents for electric stator and rotor fault diagnosis. A simulation and experimental validation for inter-turn stator short-circuit electric fault and end-ring broken rotor fault diagnosis was performed. The main objective of the work is to perform a non invasive electric fault diagnosis to avoid economical losses in the industrial process using the advantages of spectral and wavelet tools.